The river between us - Peck, Richard (New York Penguin Books, 2003)
During the early days of the Civil War, the Pruitt family takes in two mysterious young ladies who have fled New Orleans to come north to Illinois.
Keywords: Racially mixed people -- Fiction; Family life -- Illinois -- Fiction; Race relations -- Fiction; New Orleans (La.) -- Social life and customs -- 19th century -- Fiction; Illinois -- History -- 1778-1865 -- Fiction